Data inventory, processing, and reporting on plant blindness among high school students in three schools in West Java - Soraya, Puan Helwa Rezha; Solihat, Rini; Sanjaya, Yayan; Harada, Taro (Universitas Negeri Jakarta, 2025)
Plant blindness is a problem related to a person's inability to realize, recognize, and know the benefits and roles of plants. After some research, there was a shift in the term, from Plant Blindness to Plant Awareness Disparity. This study aims to find out the prevalence of Plant Blindness in three high schools in West Java. The method used in this study is descriptive Cross sectional. The results of this study revealed that there were differences in the level of plant awareness in the three schools studied. One of the schools in the city of Bandung showed the highest plant awareness rate. In addition, it was also found that students who had a high level of plant awareness had a high perception of plant awareness. As a follow-up, further research can be carried out to collect more data so that it becomes a whole population. In addition, researchers can then use additional instruments so that more things can be revealed about plant blindness.